MICROPINOCYTOSIS CHANGES IN MYOCARD BLOOD CAPILLARIES OF AGING RATS WITH INNATE HYPOTHYROIDISM - Чухрай, С.М. (World of Medicine and Biology, 2016)
Blood capillaries of 7, 45, 100 and 240 days rats with innate hypothyroidism (IHT) were researched using ultrastructural morphometric analysis. Intensity of transcytosis was evaluated by level of volume and quantitative density of micropinocytotic vesicles (MPV), their average section area and form factor. All measurements were performed with semiautomatic equipment for graphical images processing.It was found that in 7-day rats with IHT quantity indicators of micropinocytosis intensity in endothelial cells of myocard blood vessels showed no valid difference with age control group. In 45-day rats with IHT processes of transendothelial transmission of substances increased that is demonstrated by increase in quantity density of MPV. There are some cells whose peripheral areas are filled with MPV. The volume density of MPV remains statistically the same with its level in the control group that is most probably connected with simultaneous increase of number and decrease of size of these structures.In 100-day rats with IHT the quantitative density of MPV exceeded both 45-day rats with IHT and control levels. Such increase might reflect reinforcement of transcytosis and have compensatory meaning.In 240-days rats with IHT there is a substantial decrease in MPV number and their fusion that is one of the indicators of compensatory processes fail in myocard endothelium blood capillaries.
Keywords: innate hypothyroidism; rats; micropinocytosis; electron microscopy; morphometry